Identifikasi dan Karakterisasi Sumber Daya Genetik Buah-Buahan Lokal di Kabupaten Klungkung - ANELIA REZKINA BR.S; I NYOMAN RAI; IDA AYU MAYUN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Identification and Characterization of Genetic Resources Local Fruits in Klungkung RegencyLocal fruit is all kinds of fruits which are developed and cultivated in Bali, while the local fruit products are all results and proceeds derived from plants which are local fruit that still fresh or have been processed. The aims of this study were to identify the types of genetic resources local fruits in Klungkung Regency, profiling the genetic resources of local fruits concerning the morphological characters, utilization, superior fruit, harvest time, and map of the geographical distribution of the diversity of fruits. This research was carried throughout all of Klungkung Regency (Klungkung, Banjarangkan, Dawan, and Nusa Penida District), from January to October 2015. It has three steps, which were (1) collecting of secondary data, (2) surveying types of genetic resources and distribution, (3) identifying of morphological, characters, utilization, superior fruit, harvest time and map of geographies. The result of the research showed that 26 species and 39 sub-types of local fruits spread over four districts, as well as the two commodities based on the LQ-value by Klungkung Regency which were, guava located in the Dawan Village, Dawan District, and sapodilla located at Dawan Klod Village, Dawan District.